Does Motor Competence Affect Self-Perceptions Differently for Adolescent Males and Females?. (17th November 2015) - Rose, Elizabeth; Larkin, Dawne; Parker, Helen; Hands, Beth
Little is understood about the impact of level of motor competence on self-perceptions in adolescence, in particular how this may differentially affect girls and boys. A sample of 1, 568 14-year-old participants (766 girls and 802 boys) were grouped into four motor competence levels (very low to high) based on the McCarron Assessment of Neuromuscular Development (MAND). Self-perceptions were assessed using the Self-Perception Profile for Adolescents. Boys had higher self-perceptions of global self-worth, athletic competence, and physical appearance, whereas girls had higher scores for close friendships and behavioral conduct. Main effects in the predicted direction were found for motor competence for self-perceptions of global self-worth, athletic competence, physical appearance, close friendships, social acceptance, and romantic appeal. These findings indicate that level of motor competence is important in many aspects of self-perceptions, affecting girls and boys differently. Higher motor competence has a protective effect on psychosocial health, particularly for girls.